2019
DOI: 10.5039/agraria.v14i2a5656
|View full text |Cite
|
Sign up to set email alerts
|

Leaf area estimation in triticale by leaf dimensions

Abstract: The objective of this study was to estimate the leaf area of triticale in function of linear dimensions from flags and other (non-flag) leaves. An experiment was conducted with the IPR111 cultivar in the 2016 agricultural year. At 93 days after sowing, 400 leaves were collected in order to generate the mathematical models of leaf area estimation in function of linear leaf dimensions. A total of 200 leaves were collected at 106 days after sowing in order to validate the models. In each of the 600 leaves, the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…Minimum, maximum, mean, total amplitude, median, variance, standard deviation, standard error, and coefficient of variation for length (L), width (W), product of length by width (L.W), and real leaf area (LA) of 200 Psychotria colorata leaf blades. Scatterplots between L, W, L.W, and LA showed different dispersion patterns (Figure 3), indicating that the data fit linear and non-linear regression models, as found in other similar studies (Toebe et al 2019;Ribeiro et al 2020b). Figure 4 shows the leaf area percentage distribution by different intervals.…”
Section: Resultssupporting
confidence: 79%
“…Minimum, maximum, mean, total amplitude, median, variance, standard deviation, standard error, and coefficient of variation for length (L), width (W), product of length by width (L.W), and real leaf area (LA) of 200 Psychotria colorata leaf blades. Scatterplots between L, W, L.W, and LA showed different dispersion patterns (Figure 3), indicating that the data fit linear and non-linear regression models, as found in other similar studies (Toebe et al 2019;Ribeiro et al 2020b). Figure 4 shows the leaf area percentage distribution by different intervals.…”
Section: Resultssupporting
confidence: 79%
“…Among the 1,452 leaves used for generation and among the 363 leaves used for validation of the models, the CV of the length x width product (LW) of the leaf blade and leaf area (Y) was approximately twice the CV of the length (L) and width (W) of the leaf blade (Table 2). A similar pattern was observed in leaves of coccoloba (Mariano et al, 2009), snap bean (Toebe et al, 2012), forage turnip (Cargnelutti et al, 2012), pigeon pea (Cargnelutti et al, 2015), yacon (Cunya et al, 2017), sunn hemp (Carvalho et al, 2017), dwarf pigeon pea (Pezzini et al, 2018), triticale (Toebe et al, 2019), and coffee (Cavallaro et al, 2020).…”
Section: Resultssupporting
confidence: 61%
“…In the scatter plots, it is observed that there are patterns of nonlinearity between L and Y and between W and Y and linearity between LW and Y, which suggests better fit of nonlinear and linear models, respectively (Figure 2). These patterns have also been verified in forage turnip (Cargnelutti et al, 2012), pigeon pea (Cargnelutti et al, 2015), sunn hemp (Carvalho et al, 2017), and triticale (Toebe et al, 2019).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations